Epidemiological characteristics of pediatric consultations at the emergency services of a public hospital in the interior of Uruguay in 2019: Uruguay 2019 (Archives of Pediatrics of Uruguay, 2022)
The School Hospital Hospital Escuela del Litoral de Paysandú is a departmental and regional reference center with a unique Emergency Service. It serves 68,000 users, 25% of which are pediatric users.Objectives: to describe the total epidemiology consultations in 2019 at the Emergency Service of the Hospital Escuela del Litoral de Paysandú and the characteristics of its emergency pediatric population. Analyze the key reasons for consultation, care demand, level of severity, the role of doctors who receive pediatric patients and patients’ referral.Material and methods: retrospective descriptive study of the demand for care in 2019. Description and analysis of pediatric consultations between January 1 and June 30, 2019. Results: 47,647 consultations, 11,411 pediatric. Months of greater consultation: July, August and October. N: 4905. 34.4% preschool. 89% of the consultations were classified as level 4 and 5. Respiratory pathology prevailed in all age groups and months of the year. Level 1 patients were referred to moderate care or ICU and one died.Discussion and conclusions: higher demand for care in Winter months due to respiratory pathologies. 1 out of every 100 consultations belonged to Emergency-Urgency Services and 1 out of 5 were less urgent. Inadequate use of the Emergency Service with care overload. We confirm the effectiveness of Triage as a tool in a mixed Emergency Services patients’ referral process.
Keywords: Emergency medical services; Pediatrics; Epidemiology